Immune Complexes of Beta-2-Glycoprotein I and IgA Antiphospholipid Antibodies Identify Patients With Elevated Risk of Thrombosis and Early Mortality After Heart Transplantation - Serrano, Manuel; Morán, Laura; Martinez-Flores, Jose Angel; Mancebo, Esther; Pleguezuelo, Daniel; Cabrera-Marante, Oscar; Delgado, Juan; Serrano, Antonio (Frontiers in Immunology, 2019)
The presence of anti-Beta 2 glycoprotein antibodies (aB2GP1) of IgA isotype is common in patients with functional impairment of the organs in which B2GP1 is elaborated. Pretransplant IgA aB2GP1 has been associated with increased risk of thrombosis in kidney and heart transplanted patients and has also been related with early mortality after heart transplantation. Circulating immune com¬plexes between IgA and B2GP1 (B2A-CIC) have been described in the blood of patients positive for IgA aB2GP1 with thrombotic clinical symptoms. In kidney transplanted patients, B2A-CIC is a biomarker that predicts which patients IgA aB2GP1 positive are at risk of thrombosis events following kidney transplantation and may lead to early prophylactic treatment. The prevalence of B2A-CIC and its relation with outcomes after heart transplantation is not known. Methods: Follow-up study based on 151 consecutive patients who received a heart transplant. Autoantibodies and B2A-CIC were quantified in pre-transplant serum samples. Three groups of patients were followed-up for two years: Group-1, positive for IgA aB2GP1 and B2A-CIC (N=19). Group-2, only positive for IgA aB2GP1 (N=28). Group-0 (control group): IgA aB2GP1 negative (N=104). Results. Kaplan-Meir survival analysis showed that mortality in B2A-CIC positive was higher than group-0 at 3 months (HR:5.08; 95%CI: 1.36-19.01) and at 2 years (HR:3.82; 95%CI: 1.54-12.66). No significant differences were observed between group-2 and group-0. Multivariate analysis identified B2A-CIC as the most important independent risk factor for early mortality (OR=6.12; 95% CI:1.93-19.4). Post-transplant incidence of thrombosis was significantly higher in B2A-CIC positive patients than in the control group (OR:6.42; 95%CI: 2.1-19.63). Multivariate analysis identified the presence of B2A-CIC (OR:6.13; 95%CI:2.1-19.63) and the pre-transplant habit of smoking actively (OR:4.18; 95%CI:1.35-12.94) as independent risk factor for thrombosis. The proportion of patients who had thrombotic events or died in the first trimester was significantly higher in group-1 (73.7%) than in group-0 (16.3%; p<0.001) and in group-2 (39.3%; p=0.02). Multivariate analysis identified B2A-CIC as the main independent risk factor for early outcomes (mortality or thrombosis) in the first three months after heart transplant (OR=11.42, 95% CI: 1.69-9.68). Conclusion: B2A-CIC are a predictor of early mortality and thrombosis after heart transplant.